Pengaruh Oral Motor Stimulation terhadap Kemampuan Mengisap pada Bayi Berat Badan Lahir Rendah (BBLR) di RSUP Prof. Dr. I. G. N. G Ngoerah Denpasar Bali - Agung Ayu Winda P., Anak; Tirtawati, Dewi (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background : Low Birth Weight Infants (LBWIs) often have underdeveloped oromotor abilities, leading to insufficient sucking and swallowing mechanisms. Oral motor stimulation, involving touch and stimulation, especially in the muscle tissues around the mouth, can enhance blood circulation, improve muscle function, and stimulate sucking reflexes in infants. Objectives : This study aims to determine the influence of oral motor stimulation on the sucking ability of low birth weight infants (LBWIs) at RSUP Prof. Dr. I. G. N. G Ngoerah Denpasar Bali. Methods : The research conducted is an experimental study with a one-group pre-test-post-test design. Purposive sampling was used to select 21 LBWIs facing sucking difficulties at RSUP Prof. Dr. I. G. N. G Ngoerah Denpasar Bali. Respondents received intervention once a day for 5 minutes over 7 consecutive days, 15 minutes before feeding. The collected data were presented descriptively, and normality was tested using the Shapiro-Wilk test. Results : Data analysis using the non-parametric Wilcoxon Signed Test showed a significant influence of oral motor stimulation on sucking ability with a significance value (p=0.000) < 0.05. Conclusion : Oral motor stimulation can improve sucking ability in low birth weight (LBW) babies. Keywords : Oral Motor Stimulation, Sucking Ability, Low Birth Weight Infants (LBWIs)